Distribution of food items of six commercially important demersal fishes in the South China Sea - Ibrahim, Sakri; Muhammad, Muhaimi; Ambak, Mohd Azmi; Zakaria, Mohamad Zaidi (Universiti Putra Malaysia Press, 2004)
Distribution of food items of six commercially important fish species in waters off the east coast of Peninsular Malaysia were studied. Trawl surveys were conducted in 124 stations in areas between 12 to 200 nautical miles from shore covering an estimated area of 27,785.54 square nautical miles. Stomachs offish species collected were removed on board, preserved and taken to the laboratory for analysis of the contents. The occurrence method was used to quantify the diet. Penaeus sp. was found to be the main food item of Carangoides malabaricus, Nemipterus marginatus, Priacanthus tayenus, and Upeneus bensasi while Loligo sp. for Saurida undosquamis and Sphyraena forsteri. Sub-areas 0, 1, II and III appeared to be the most productive areas for the studied species and the food items. The results also show that there exist significant relationships between the food items and fish distribution. Information on the availability and distribution of food items is important for the management of fishery resources as well as for the efficient exploitation of the species.